The Relationships of Parenting Patterns and Excellence With the Level of Radicalism in Senior High School Students - Rachmatianto, Alif; Freyani Hawadi, Lydia (KnE Social Sciences, 2022)
This study focused on parenting, individual assessment and radicalism, and discussed their validity and reliability in high school students. A total of 178 students from several schools in the City X area were involved as participants. The results indicated that there was a positive relationship between parenting and radicalism, and also a relationship between excellence and radicalism. Keywords: radicalism, individual values, parenting